Iconoclasm and iconoclash : struggle for religious identity - Asselt, W. J. van. (Jewish and Christian Perspectives Series, 2007)
This book focuses on iconoclastic controversies and, in particular, their impact on the creation of religious identities. In the history of Jewish, Christian and Muslim culture, religious identity was not only formed through historical claims, but also through the use of certain images: 'images of God', 'images of the others', and 'images of the self.' Moreover, in the struggle for religious identity these 'images' were time and again employed for the purpose of establishing distinct groups, both ortho- dox and deviant. At the same time, they supplied weapons in the theological debate and found explicit expression in certain rituals or liturgical traditions. These conference proceedings include a discussion of the role of images in society, politics, theology and liturgy, in particular addressing the 'iconoclash' of physical, mental and verbal images on the construction of religious identity.